Palestinian Chicago Identity in Exile - Lybarger, Loren (University of California Press, 2020)
"Chicago is home to one of the largest, most politically active Palestinian immigrant communities in the United States. For decades, secular nationalism held sway as the dominant political ideology, but since the 1990s its structures have weakened and Islamic institutions have gained strength. Drawing on extensive fieldwork and interview data, Palestinian Chicago charts the origins of these changes and the multiple effects they have had on identity across religious, political, class, gender, and generational lines. The perspectives that emerge through this rich ethnography challenge prevailing understandings of secularity and religion, offering critical insight into current debates about immigration and national belonging. "Provides the first in-depth examination of an important Palestinian-American community in a major US city. This book is a welcome contribution to our understanding of both the Palestinian diaspora and an important US immigrant community." RASHID KHALIDI, author of The Hundred Years' War on Palestine "In this groundbreaking and beautifully written book, Loren Lybarger centers the voices of a wide array of Palestinians and brings forth the complex, dynamic, and fluid ways members of this community navigate identity and belonging in today's world." MAHA NASSAR, author of Brothers Apart: Palestinian Citizens of Israel and the Arab World "Palestinian Chicago masterfully transforms existing understandings of Palestinian identity, resistance, and diaspora. This is an extraordinarily valuable text for anyone interested in history, ethnic studies, urban studies, religious studies, and Middle East studies." NADINE NABER, author of Arab America: Gender, Cultural Politics, and Activism "A compelling work that complicates the secular in Palestine and the Arab world, in diaspora, and in the United States." SHERENE SEIKALY, author of Men of Capital: Scarcity and Economy in Mandate Palestine"